Motivation of Learning English; A Case of Indonesian Migrant Worker's Children in Malaysia - Damai Lestari; Ana Maghfiroh; Diyah Atiek Mustikawati (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
Motivation is one of the key components of learning. Researchers have begun to consider these motivations as a result of the extremely rapid increase in the interest of learning the foreign languages. This study aims to investigate the studentsÔÇÖ motivation at SB Kampung Bharu in Kuala Lumpur, Malaysia in learning a foreign language. This research employs a mixed method where the data obtained through questionnaires. The quantitative data was calculated and categorized using the presentation, while the qualitative data was analyzed using Miles and Huberman methods including data reduction, data display, and conclusion. Students from grades VI and V at SB Kampung Bharu in Kuala Lumpur, Malaysia, were the subject of the research. The results showed that student motivation for learning foreign languages was quite high. It can be seen from the quantitative data that revealed the students' motivation to learn foreign languages were 40% always, 48% often, 68% sometimes, 16% rarely, and 16% never during the English learning process. In particular, there is a fairly high indicator produced where students have a fairly high interest and motivation to learn foreign languages both internally and externally, so that students can succeed their English language learning process with the support of this motivation.